2019
DOI: 10.1063/1.5099089
|View full text |Cite
|
Sign up to set email alerts
|

Control effect of micro vortex generators on attached cavitation instability

Abstract: The control effect of micro-vortex generators (VGs) on the instability of attached cavitation was investigated in a series of experiments. The micro-VGs, located at the leading edge of a NACA0015 hydrofoil, were used to alter the near-wall flow and control the attached cavitation dynamics. The effect of the nondimensional height of micro-VGs on the nondimensional cavity length was quantitatively evaluated by regression equations through response surface methodology. The micro-VGs increased the nondimensional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…In another study, Che and coauthors analyzed the instability of the attached cavitation produced with mVGs. 186 This study confirmed that these mVGs are an effective passive control for attached cavitation dynamics and changed the surface wall's vicinity's flow dynamics. The results also emphasized again that the mVGs could increase the cavity length and induce counter-rotating streamwise vortices.…”
Section: Physics Of Fluidssupporting
confidence: 72%
See 2 more Smart Citations
“…In another study, Che and coauthors analyzed the instability of the attached cavitation produced with mVGs. 186 This study confirmed that these mVGs are an effective passive control for attached cavitation dynamics and changed the surface wall's vicinity's flow dynamics. The results also emphasized again that the mVGs could increase the cavity length and induce counter-rotating streamwise vortices.…”
Section: Physics Of Fluidssupporting
confidence: 72%
“…In this study, Che et al 186 interpret two types of Rayleigh-Taylor (R-T) and K-H instabilities, while cavity shedding and re-entrant jet interactions happened over a smooth hydrofoil and hydrofoil with mVGs. Re-entrant jets are generated by exposing cavity closure to an adverse pressure gradient.…”
Section: Physics Of Fluidsmentioning
confidence: 79%
See 1 more Smart Citation
“…Realistic actuation mechanisms, such as plasma actuators (Sato et al, 2015), suction mechanisms (Wang et al, 2016), transverse motion (Li & Aubry, 2003), periodic oscillations (Lu et al, 2011), oscillating foils (Bao & Tao, 2013), air jets (Zhu et al, 2019), or Lorentz forces in conductive media (Breuer et al, 2004), are also discussed in details, as well as limitations imposed by real-wold systems (Belson et al, 2013). Similarly, a lot of experimental work has been performed, with the goal of controlling either the cavitation instability (Che et al, 2019), the vortex flow behind a conical forebody (Meng et al, 2018), or the flow separation over a circular cylinder (Jukes & Choi, 2009a,b). arXiv:1906.10382v2 [physics.comp-ph] 12 Aug 2019 ACCELERATING DRL OF AFC: MULTI-ENV APPROACH AUGUST 13, 2019 Finally, while most of the literature has focused on complex, closed-loop control methods, some open-loop methods have also been discussed, both in simulations (Meliga et al, 2010) and in experiments (Shahrabi, 2019).…”
mentioning
confidence: 99%
“…Finally, the selected spectrum band is taken as the envelope spectrum, and demodulated signals can be obtained by inverse Fourier Transform (FT), so the feature extraction from the envelope spectrum can detect the hidden non-stationarities of measured signals. Here, Kurtosis is used to describe the degree of steepness of a random distribution, as defined in Equation (2). It has been widely used to detect the impact fault in rotating machinery [20][21][22][23][24][25][26].…”
Section: Autogram Compared With the Kurtogrammentioning
confidence: 99%